2016
DOI: 10.1016/j.neurobiolaging.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Frontostriatal anatomical connections predict age- and difficulty-related differences in reinforcement learning

Abstract: Reinforcement learning (RL) is supported by a network of striatal and frontal cortical structures that are connected through white-matter fiber bundles. With age, the integrity of these white-matter connections declines. The role of structural frontostriatal connectivity in individual and age-related differences in RL is unclear, although local white-matter density and diffusivity have been linked to individual differences in RL. Here we show that frontostriatal tract counts in young human adults (aged 18-28),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…Indeed, age-related changes in dopaminergic processing are not limited to the striatum: a recent meta-analysis suggested similar age-related declines in dopaminergic receptor and transporter availability in the striatum, frontal cortex, and midbrain (Karrer et al, 2017). Recently, we have also demonstrated that different networks of frontostriatal connections are related to RL performance in older compared to young adults, including additional tracts between the striatum and lateral PFC (van de Vijver et al, 2016). Thus, further research including neuroimaging measures is needed to increase our understanding of age-related changes in the balance between brain networks related to WM and low-level, RPE-based learning to support RL.…”
Section: The Role Of Working Memory In Instrumental Learningmentioning
confidence: 82%
See 2 more Smart Citations
“…Indeed, age-related changes in dopaminergic processing are not limited to the striatum: a recent meta-analysis suggested similar age-related declines in dopaminergic receptor and transporter availability in the striatum, frontal cortex, and midbrain (Karrer et al, 2017). Recently, we have also demonstrated that different networks of frontostriatal connections are related to RL performance in older compared to young adults, including additional tracts between the striatum and lateral PFC (van de Vijver et al, 2016). Thus, further research including neuroimaging measures is needed to increase our understanding of age-related changes in the balance between brain networks related to WM and low-level, RPE-based learning to support RL.…”
Section: The Role Of Working Memory In Instrumental Learningmentioning
confidence: 82%
“…Additionally, it is a first indication of how the mechanisms supporting RL may vary depending on the timescale of learning. As older adults seem to use different frontostriatal brain networks than young adults do to process performance feedback and improve behavior (van de Vijver et al, 2016;van de Vijver, Cohen, & Ridderinkhof, 2014), the investigation of the interplay between cortical and subcortical changes and the related cognitive implications may provide promising insights into the dynamics of age-related changes in behavioral adaptation, and the differences therein with different timescales of learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, learning the correct contingencies of the orthogonalized go/no-go task may critically rely on high-level cognitive functions, thus lifespan differences reported here may also relate to interindividual differences in working memory and long-term memory. These cognitive functions may also be compromised as a result of age-related decline in grey and white matter integrity (Draganski et al , 2011; Samanez-Larkin et al , 2012, Chowdhury et al , 2013 b ; Callaghan et al , 2014; Acosta-Cabronero et al , 2016; Steiger et al , 2016; van de Vijver et al , 2016) which may influence the ability of the instrumental system to learn the task contingencies as indexed by learning rate, reward and punishment sensitivity. Therefore, the effect of decreased dopamine function on the strength of the Pavlovian system may be shadowed by the effects of an age-related decrease in executive functions or instrumental abilities related to structural decline.…”
Section: Discussionmentioning
confidence: 99%
“…Integrity of frontostriatal pathways as measured by diffusion weighted imaging (DWI) has previously proven the important of good performance in probabilistic reward learning tasks which measure value-based decision-making ability ( Samanez-Larkin et al. 2012 ; van de Vijver et al. 2016 ).…”
Section: Introductionmentioning
confidence: 99%